2005
DOI: 10.1088/0953-8984/17/21/029
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence of Bi3+in Y3Ga5O12single-crystal host

Abstract: Photoluminescence spectra and decay kinetics within 10-350 K were measured in the Bi-doped Y 3 Ga 5 O 12 single crystal prepared by the micro-pullingdown technique. Temperature dependences of the decay times and the integrated emission intensities obtained from the experiment were simulated using a phenomenological two-excited-state-level model. The model provided quantitative parameters of the involved excited state levels of the Bi 3+ luminescence centre in this host. The results are discussed in the light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 28 publications
(41 reference statements)
8
66
0
Order By: Relevance
“…Comparison of the data obtained for YAG:Bi in the present paper and for LuAG:Bi by Babin et al (2009) with those reported for the UV emission of Bi 3þ centers in other hosts (see, e.g., Wolfert and Blasse, 1985;Donker et al, 1989;Aceves et al, 1996;Nikl et al, 2005) allows us to conclude that the 5.9 eV and 4.57 eV excitation bands arise from the electronic transitions to the singlet and The intensity of the UV band is decreased 10 times. The spectra are distorted around 2.7 eV due to the contamination of the samples with Ce 3þ ions and the reabsorption of the VIS emission in the z2.7 eV absorption band of Ce 3þ centers.…”
Section: Ultraviolet Luminescencesupporting
confidence: 76%
See 3 more Smart Citations
“…Comparison of the data obtained for YAG:Bi in the present paper and for LuAG:Bi by Babin et al (2009) with those reported for the UV emission of Bi 3þ centers in other hosts (see, e.g., Wolfert and Blasse, 1985;Donker et al, 1989;Aceves et al, 1996;Nikl et al, 2005) allows us to conclude that the 5.9 eV and 4.57 eV excitation bands arise from the electronic transitions to the singlet and The intensity of the UV band is decreased 10 times. The spectra are distorted around 2.7 eV due to the contamination of the samples with Ce 3þ ions and the reabsorption of the VIS emission in the z2.7 eV absorption band of Ce 3þ centers.…”
Section: Ultraviolet Luminescencesupporting
confidence: 76%
“…However, the luminescence of Bi 3þ centers in garnets has been studied in only a few papers. In the emission spectrum of Y 3 Ga 5 O 12 :Bi (Nikl et al, 2005;Setlur and Srivastava, 2006), Gd 3 Ga 5 O 12 :Bi (Setlur and Srivastava, 2006), Y 3 Al 5 O 12 :Bi (Setlur and Srivastava, 2006;Zorenko et al, 2007Zorenko et al, , 2009, and Lu 3 Al 5 O 12 :Bi (Setlur and Srivastava, 2006;Zorenko et al, 2009), two bands were observed, located in the ultraviolet and the visible spectral range. The ultraviolet emission was ascribed to the radiative decay of the triplet excited state of Bi 3þ .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Bi 3+ -doped rare-earth aluminate and gallate garnets, where a Bi 3+ ion substitutes for a trivalent rare-earth ion, can be considered as perspective materials for scintillators due to an intense and fast Bi 3+ -related emission [1][2][3]. In SCFs of Bi 3+ -doped aluminum garnets prepared by the liquid phase epitaxy (LPE) method, a large and variable concentration of Bi 3+ ions can be achieved [3].…”
Section: Introductionmentioning
confidence: 99%